Association Between Vitamin D Deficiency And Suicide Attempts In Patients With Major Depressive Disorder : Association between Vitamin D Deficiency and Suicide Attempts - Memon, Zahoor Ahmed; Ambreen, Syeda; Lakho, Arshad Sattar; Abro, Akbar Gohar; Bashir, Saba; Shah, Hanozia (Pakistan Journal of Health Sciences, 2024)
Major Depressive Disorder (MDD) is significant public health concern that is often associated with an increased risk of suicide attempts. Emerging research suggests that Vitamin D3, a nutrient primarily obtained through sunlight exposure and certain foods, plays a crucial role in brain health and mood regulation and thus affects various psychiatric disorders, including depression. Objective: To determine the association between decreased Vitamin-D levels and a history of attempted suicide among patients suffering from Major Depressive Disorder. Methods: A comparative cross-sectional study was carried out from December 2020 to June 2021, on a sample of 104 patients diagnosed with Major Depressive Disorder. Half of the samples were with Vitamin-D3 deficiency while half of the sample were without Vitamin-D3 deficiency. This research was carried out at the Department of Psychiatry and Behavioral Sciences, Liaquat University Hospital, Hyderabad, Pakistan. Data were analyzed with SPSS version 21.0. Results: The mean age of the sample stood at 44 years (09 ± SD). A majority of the sample comprised of male (55.77%), hailing from an urban background and a middle socioeconomic set-up (60.58%). The mean Vitamin-D level was 18.63 ng/ml, while the mean Vitamin-D3 level was 14.77 ng/ml and 22.05 ng/ml for groups A and B respectively. History of attempted suicide was more prevalent among patients with Vitamin D3 deficiency. Conclusion: The research concluded that Vitamin-D deficiency is found to be one of the factor for suicidal attempts in patients with Major Depressive Disorder.